Whole-Cell Protein Profiles of Disintegrated Freshwater Green Algae and Cyanobacterium. Issue 1 (2nd January 2016) - Samek, Dušan; Mišurcová, Ladislava; Machů, Ludmila; Buňková, Leona; Minařík, Antonín; Fišera, Miroslav
ABSTRACT: The influence of cultivation methods and postharvesting treatment on protein profiles of green freshwater microalgae Chlorella kessleri, Scenedesmus quadricauda, and Chlorella sp. and cyanobacterium Spirulina platensis were evaluated. The comparison of protein profiles in algal biomass originated from the autotrophic cultivation in an outdoor open circulating cascade-type cultivation apparatus in thin-layer, a solar photobioreactor, and from the heterotrophic cultivation regime in a fermenter. All tested algae contained protein bands in the area between 14.3–27 and 70–116 kDa. Protein profiles revealed much higher heterogenity in the area between 30–70 kDa.